Mengoptimalkan Perkembangan Belajar Siswa Kelas V SDI Pelita Hati Lenteng Sumenep - Wardatul Hasanah Elqamariyah; Fachrur Rozie (Pusat Riset dan Inovasi Nasional, 2023)
One of the efforts to optimize student learning development is to make communication patterns between teachers and parents. By implementing a pattern of communication between teachers and parents, it will make student learning monitored by teachers at school and parents at home. The purpose of this study was to find out the communication patterns used by teachers and parents of fifth grade students at SDI Pelita Hati and the impact they had on the communication patterns between teachers and parents of fifth grade students at SDI Pelita Hati Lenteng Sumenep. This research uses a qualitative approach using a descriptive research type. Data was collected using interviews, observation, and documentation. The results of the study show that teachers and parents use wheel communication patterns and star communication patterns in the communication pattern models that teachers and parents use. Meanwhile, in the implementation of communication patterns, two-way communication patterns and multi-way communication patterns are also used. The impact of teacher and parent communication patterns based on the results of interviews and observations is that it can make it easier for parents or teachers to obtain information about student development, can channel thoughts that are obtained by teachers and parents, and can improve attitudes and behavior that are not good in teachers, parents and also students.